Interpreting the Spent Cost for Water Supply and Transmission Projects in Semnan Province - Mohammad Arabpanahan; Iraj Heidarian (علوم و مهندسی آب و فاضلاب, 2019)
Significant shortage of water resources capacities, especially in central Iran’s desert basins, necessitates construction and implementation of water supply and transmission facilities. Costs of such projects have effects on water pricing and consumption management. For water, with final consumption nature, achieving real price based on demands is important in encouraging the private sector contribution and improvement of drinking water consumption pattern. Current study, based on documented database, calculates spent cost for accomplishing such above-mentioned projects in Semnan province, Iran. Results showed that for water supply and transmission projects, there was a significant difference between spent cost and common established tariff. Actually, it was confirmed that currently, water is not considered as an economic good with meaningful concept of benefit or loss. According to the current pricing system, improvements in consumption management could not be expected, especially in drinking water uses.